Clinical features and prenatal risk factors for hypertensive disorders in twin pregnancies. Issue 6 (June 2014) - Taguchi, Takako; Ishii, Keisuke; Hayashi, Shusaku; Mabuchi, Aki; Murata, Masaharu; Mitsuda, Nobuaki
Abstract Aim The aim of this study was to identify the incidence, clinical features, and prenatal risk factors for hypertensive disorders, including gestational hypertension (GH) and pre‐eclampsia (PE), in twin pregnancies. Material and Methods We carried out a retrospective cohort study of twin pregnancies managed from the first trimester onward at a single center from 2002 through 2011. We retrospectively evaluated the incidence, severity, time‐point onset of GH or PE, as well as maternal and neonatal outcomes. Prenatal risk factors for disease were also analyzed with a multivariable logistic regression model. Results Of 742 twin pregnancies, 165 (22%) were diagnosed with GH or PE. Five women developed GH or PE at <32 weeks' gestation (early onset), and the remaining 160 developed them at ≥32 weeks (late onset). Of all 165 cases, 110 women (66.7%) developed their disease during the intrapartum or postpartum period. The significant risk factors associated with developing a hypertensive disorder in a twin pregnancy were primiparity (adjusted odds ratio [aOR]: 1.77; 95% confidence interval [CI]: 1.21–2.61), pregestational high body mass index (aOR 1.35, 95%CI: 1.08–1.70), family history of hypertension (aOR: 1.50; 95%CI: 1.02–2.17) and previous history of GH or PE (aOR 8.85; 95%CI: 2.70–29.0). Conclusions One‐fifth of the twin pregnancies developed GH or PE. Furthermore, more than half of the patients were diagnosed with the disease during the intrapartum or postpartum period. Significant risk factors for GH or PE in twin pregnancies were primiparity, pregestational body mass index, family history of hypertension, and history of a hypertensive disorder during a previous pregnancy. The significance of monitoring blood pressure after delivery for a twin pregnancy is stressed.